2017
DOI: 10.1007/s10495-017-1376-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of glycogen synthase kinase following myocardial infarction and ischemia–reperfusion

Abstract: Glycogen synthase kinase-3 beta (GSK3β) is principally is a glycogen synthase phosphorylating enzyme that is well known for its role in muscle metabolism. GSK3β is a serine/threonine protein Kinase, which is responsible for several essential roles in mammalian cells. This enzyme is implicated in the pathophysiology of many conditions involved in homeostasis and cellular immigration. GSK3β is involved in several pathways leading to neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…We focused the attention on glycogen synthase kinase-3 β (GSK3β) for two main reasons. First GSK3β can be activated under specific stress-conditions and it is involved in the regulation of cell death pathways in different cellular contexts [23][24][25][26][27] . Second, among other represented hits interacting proteins, regulators and substrates of GSK3β were found.…”
Section: Resultsmentioning
confidence: 99%
“…We focused the attention on glycogen synthase kinase-3 β (GSK3β) for two main reasons. First GSK3β can be activated under specific stress-conditions and it is involved in the regulation of cell death pathways in different cellular contexts [23][24][25][26][27] . Second, among other represented hits interacting proteins, regulators and substrates of GSK3β were found.…”
Section: Resultsmentioning
confidence: 99%
“…We humbly write to thank Zhi-Qing Chen et al for their letter where they have pointed out the miswritten difference we have reported in molecular structure in our already published paper between GSK-3α and GSK-3β2 and to express our deepest apologies for this miswritten phrase in our paper [1]. We totally agree with Zhi-Qing Chen et al that GSK-3α occupies a domain with 13 amino acids inserts at the N-terminal of GSK-3α and not GSK-3β2.…”
mentioning
confidence: 89%
“…Due to its extensive participation in signalling pathways (in addition to its metabolic role of regulating glycogen synthesis), glycogen synthase kinase (GSK)-3β is one of Akt's most prominent downstream targets in mediating mitochondrial protection [76]. In hypoxia, GSK-3β is activated by phosphorylation of its Tyr 216 [77], and contributes to the hypoxia or ischemia-induced tissue injury.…”
Section: Akt's Effects On Glycogen Synthase Kinase-3β-mediated Processesmentioning
confidence: 99%
“…The diminished binding of the transcription factor results in a reduced expression of Nrf2/ARE-regulated genes encoding proteins of the antioxidant defence system, such as superoxide dismutase, peroxidase, catalase, and enzymes of glutathione synthesis and reactivation [78]. The resulting oxidative stress damages the mitochondria, which significantly contributes to hypoxia or ischemia-induced mitochondrial impairments and tissue injury [76]. Furthermore, the activation of GSK-3β diminishes nuclear translocation of the transcription factor cAMP response element-binding protein (CREB), thereby diminishing CREB's binding to the co-activator CREB-binding protein (CBP) [79].…”
Section: Akt's Effects On Glycogen Synthase Kinase-3β-mediated Processesmentioning
confidence: 99%
See 1 more Smart Citation